Association between serum calcium levels and prognosis, hematoma volume, and onset of cerebral hemorrhage in patients undergoing hemodialysis - Kitamura, Mineaki (BMC Nephrol, 2019)
BACKGROUND: High serum calcium levels should be avoided in patients on hemodialysis (HD) because they can induce cardiovascular diseases and worsen the patient’s prognosis. In contrast, low serum calcium levels worsen the prognosis of patients with cerebral hemorrhage in the general population. So far, whether serum calcium levels in patients on HD are associated with cerebral hemorrhage remains unknown. This study aimed to reveal the association between serum calcium and cerebral hemorrhage in patients on HD, including in-hospital death, volume of hematoma, and onset of cerebral hemorrhage. METHODS: This cross-sectional case-control study included 99 patients on HD with cerebral hemorrhage at a single center between July 1, 2007 and December 31, 2017. Controls included 339 patients on HD at a single HD center between July 1, 2011 and June 30, 2012. Data on serum calcium level, patient demographics, and comorbid conditions were collected, and associations between cerebral hemorrhage and subsequent death were evaluated by multivariate logistic regression analysis. Further, the association of these backgrounds and hematoma volume was evaluated by multiple regression analysis. RESULTS: Of the 99 patients, 32 (32%) died from cerebral hemorrhage. The corrected serum calcium level (odds ratio [OR], 2.49; 95% confidence interval [CI], 1.43–4.35; P < 0.001) and antiplatelet drug use (OR, 3.95; 95% CI, 1.50–10.4; P = 0.005) had significant effects on the prognosis. Moreover, the corrected serum calcium (P = 0.003) and antiplatelet drug use (P = 0.01) were significantly correlated with hematoma volume. In the patients, the corrected serum calcium level (OR, 1.54; 95% CI, 1.07–2.22; P = 0.02) was associated with the onset of cerebral hemorrhage, as was pre-hemodialysis systolic blood pressure (per 10 mmHg) (OR, 1.40; 95% CI, 1.23–1.59; P < 0.001). CONCLUSIONS: Although the precise mechanisms remain unknown, a high serum calcium level is associated with cerebral hemorrhage in patients on HD. Thus, we should pay attentions to a patient’s calcium level. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12882-019-1400-4) contains supplementary material, which is available to authorized users.